Leech Farming: An Overview Over Leech Breeding and Multiplication. - Swathy, C R; Anand, P K V; Rahul , H (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: There are various descriptions regarding blood letting or Raktamoksha using leeches (Jaloukavacharana) in ayurvedic classics. Acharya Susruta considers Rakta as the fourth Dosha and mentions Raktamoksha as a Shodhana karma (purificatory therapy) and is indicated in many diseases with vitiation of Raktha. As a matter of time, leech therapy is becoming more popular due to its benefits but there is no known established reliable suppliers of leeches for medical needs especially for medal purpose, maintenance of leeches in adequate environment, reproduction of leeches and storage of leeches on a large scale. Materials and Methods: This study is based on analysis of classical ayurvedic texts, modern books and internet sources. Some help was also been taken from previous articles published on the same topic. All the relevant information are compiled here. Result :Parameters for successful leech farming are studied and application of these facts can improve leech farming and thus ensure increased availability of leeches for medical needs. Discussion: The increased demand of leeches and its lesser availability forms a challenge especially in extreme weather. Basically, leech farming is a research topic and also an innovative idea for ayurvedic scholars. Leech farming provides special knowledge regarding selection and breeding of leeches